Prophylactic furosemide infusion decreasing early major postoperative renal dysfunction in on-pump adult cardiac surgery: a randomized clinical trial - Fakhari, Solmaz (Res Rep Urol, 2017)
INTRODUCTION: Acute renal dysfunction is a common complication of cardiac surgery. Furosemide is used in prevention, or treatment, of acute renal dysfunction. This study was conducted to evaluate the protective effects of intra- and early postoperative furosemide infusion on preventing acute renal dysfunction in elective adult cardiac surgery. METHODS: Eighty-one patients, candidates of elective cardiac surgery, were enrolled in this study in either the furosemide (n=41) or placebo (n=40) group. Furosemide (2 mg/h) or 0.9% saline was administered and continued up to 12 hours postoperatively. We measured serum creatinine (Scr) at preoperative and on the second and fifth postoperative days. Then calculated estimated glomerular filtration rate (eGFR) at these times. An increase in Scr of >0.5 mg/dL and/or >25%–50%, compared to preoperative values, was considered as acute kidney injury (AKI). In contrast, an increase in Scr by >50% and/or the need for hemodialysis was regarded as acute renal failure (ARF). At the end we compared the AKI or ARF incidence between the two groups. RESULTS: On the second and fifth postoperative days, Scr was lower, and the eGFR was higher in the furosemide group. AKI incidence was similar in the two groups (11 vs 12 cases; P-value 0.622); however, ARF rate was lower in furosemide group (1 vs 6 cases; P-value 0.044). During the study period, Scr was more stable in the furosemide group, however in the placebo group, Scr initially increased and then decreased to its preoperative value after a few days. CONCLUSION: This study showed that intra- and early postoperative furosemide infusion has a renal protective effect in adult cardiac surgery with cardiopulmonary bypass. Although this protective effect cannot be discovered in mild renal dysfunctions, it apparently reduces the rate of the more severe renal dysfunctions. A more multidisciplinary strategy may be needed in reducing the milder renal damage.